Inter-individual Variability in Gut Microbiota Composition Is Associated With Changes in the Fecal Metabolome of Individuals Consuming a Military Ration Diet. (7th June 2021) - Karl, J Philip; Armstrong, Nicholes; Radcliffe, Patrick; McClung, Holly
Abstract: Objectives: The fecal metabolome provides a functional readout of interactions between host, diet and the gut microbiota that may help identify gut microbiota-derived compounds associated with health outcomes. This study aimed to determine associations between inter-individual variability in gut microbiota composition, diet-induced changes in the fecal metabolome and gastrointestinal symptoms in adults consuming a diet consisting solely of military rations. Methods: Secondary analysis of a randomized-controlled trial in which 54 healthy adults (32 ± 14 yr, BMI 26 ± 3 kg/m 2 ) were randomly assigned to consume their usual diet (Control) or a provided diet of Meal, Ready-to-Eat military rations (MRE) for 3wk. Fecal microbiota composition was measured by 16S rRNA sequencing and the fecal metabolome by untargeted UPLC-MS/MS at baseline and post-intervention. Self-reported gastrointestinal symptoms were measured weekly using the Irritable Bowel Severity Scoring System (IBSSS). Results: Principal coordinates analysis of baseline gut microbiota composition separated MRE participants into two clusters determined primarily by ratio of Bacteroides to Prevotella (HIGH ( n  = 17) or LOW ( n  = 10)). Random Forest classification of changes in the fecal metabolome within Control, HIGH, and LOW produced error rates of 7%, 18% and 100%, respectively, suggesting a more discriminant metabolome response in HIGH than LOW. Between-group differences in 153 metabolites were detected by ANOVA (FDR <0.20). Among those, 39 identified and 20 unidentified metabolites demonstrated an association with the gut microbiota (HIGH vs. LOW, P < 0.05). Compounds within xenobiotic, peptide/amino acid, and lipid metabolism pathways comprised 29 of the microbiota-associated metabolites. Changes in microbiota-associated metabolites were not correlated with changes in IBSSS scores. Conclusions: Changes in the fecal metabolome of individuals consuming a short-term military ration diet are associated with inter-individual variability in gut microbiota composition, but changes in microbiota-associated fecal metabolites do not appear to impact gastrointestinal symptoms. Funding Sources: Military Operational Medicine Research Program. Disclaimer: Authors' views do not reflect official DoD or Army policy.